Curriculum Development Strategy in Higher Education: A Study on Islamic Education in the Digital Era - Murharyana, Murharyana; Zakariah, Zakariah; Sunarya, Asep; Purba, Beno (Studi Multidisipliner: Jurnal Kajian Keislaman, 2025)
This research aims to analyze curriculum development strategies in Islamic universities in the digital era, focusing on case studies at STAI Darul Falah Cililin, West Bandung. The approach used is qualitative by using a descriptive analysis approach. The results of the study show that the curriculum development process at the institution still faces various challenges, ranging from the limitations of digital infrastructure, the lack of technology training for educators, to the lack of integration of digital-based critical thinking values in the curriculum. Nevertheless, there is optimism among academics about the potential of technology as a medium for da'wah and the enrichment of Islamic learning. Therefore, curriculum development strategies in the digital era need to be directed at strengthening institutional policies, integrating technology in learning, and intensive training for educators. With this strategy, Islamic education can be more adaptive, relevant, and able to produce graduates who think critically, creatively, and have digital competence.